2023
DOI: 10.23917/bik.v16i1.1375
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of Nursing Credentials and Recredentials by the Credentials Subcommittee at X Distric Hospital

Abstract: The results of the preliminary study indicated that the implementation of nursing credentials and recredentials by the credentials subcommittee in the hospital was not optimal. Not many studies had investigated  the problems that caused the implementation of nursing credentials and recredentials was not optimal. This research was very important to do to  explore more deeply about the problems that caused the credentials subcommittee  was not optimally  in the implementation of nursing credentials and recredent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…Indonesian Hospital Accreditation Standards 2022 emphasizes the importance of periodically conducting re-credentialing processes to ensure that medical or healthcare staff meet established standards. In Susanto's case, if the hospital had conducted re-credentialing rigorously, they might have detected Susanto's qualifications mismatch earlier and prevented him from continuing his practice as a fake doctor (Dwiantoro et al, 2023).…”
Section: Credentialing and Re-credentialing Of Hospital Staffmentioning
confidence: 99%
“…Indonesian Hospital Accreditation Standards 2022 emphasizes the importance of periodically conducting re-credentialing processes to ensure that medical or healthcare staff meet established standards. In Susanto's case, if the hospital had conducted re-credentialing rigorously, they might have detected Susanto's qualifications mismatch earlier and prevented him from continuing his practice as a fake doctor (Dwiantoro et al, 2023).…”
Section: Credentialing and Re-credentialing Of Hospital Staffmentioning
confidence: 99%
“…In SNARS edition 1.1 of 2019 on the aims and objectives of KKS 13 it is stated that the hospital ensures that every competent nurse has been credentialed by the nursing committee of the credentialing subcommittee to provide nursing care, both independent, collaborative, delegated, and mandated to patients safely and effectively (Hariyati et al, 2018). Sugito et al, (2023) in his research entitled phenomenological study of experience the nursing committee in implementing nursing credentials at the Tugurejo Regional Hospital Semarang found that the career level had not been used as a standard for determining services. The results of credentialing activities have not been felt by nurses, so they have not been motivated to apply for the next credential process.…”
Section: Introductionmentioning
confidence: 99%